Visualization of lymphatic vessels through NF-kappaB activity. - Saban, MR; Mémet, S; Jackson, D; Ash, J; Roig, A; Israël, A; Saban, R (2004)
The molecular biology of lymphatics is only rudimentary owing to the long-standing absence of specific markers, and scanty is the information regarding bladder lymphatic vessels. By using mice with a reporter gene for nuclear factor kappaB (NF-kappaB) activity (kappaB-lacZ) in combination with immunohistochemical staining with a specific lymphatic marker (LYVE-1), we show, for the first time, that NF-kappaB is constitutively active in lymphatic endothelium in the urinary bladder, uterus, intestine, heart, and airways. Tie2-lacZ mice confirmed that the structures observed in kappaB-lacZ mice were not blood vessels. In addition, acute instillation of lipopolysaccharide (LPS) or tumor necrosis factor alpha (TNF-alpha) into the kappaB-lacZ mouse bladder revealed the capacity of this transgenic in reporting inducible NF-kappaB activity. Our findings demonstrate an overriding constitutive NF-kappaB activity in the lymphatic system. They also provide a working model for detecting lymphatic vessels and evoke testable hypotheses regarding the role of lymphatic vessels in health and disease.